2017
DOI: 10.1016/j.neuron.2017.05.038
|View full text |Cite
|
Sign up to set email alerts
|

A Labeled-Line Neural Circuit for Pheromone-Mediated Sexual Behaviors in Mice

Abstract: In mice, various instinctive behaviors can be triggered by olfactory input. Despite growing knowledge of the brain regions involved in such behaviors, the organization of the neural circuits that convert olfactory input into stereotyped behavioral output remains poorly understood. Here, we mapped the neural circuit responsible for enhancing sexual receptivity of female mice by a male pheromone, exocrine gland-secreting peptide 1 (ESP1). We revealed specific neural types and pathways by which ESP1 information i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
144
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 151 publications
(154 citation statements)
references
References 46 publications
3
144
0
Order By: Relevance
“…Recent studies have shown that specific activation of aromatase neurons in the MeA promotes aggressive behaviors (Unger et al, 2015), and that reproductive sensory cues are processed by both the MeApv (Ishii et al, 2017) and the MeApd (Choi et al, 2005;Bergan et al, 2014). The overlapping control of aggressive and reproductive behaviors in the MeA mirrors the neuroethological argument that aggression is best understood as a component of reproductive behavior (Tinbergen, 1951).…”
Section: The Role Of Oxt In Mea Processing Of Sex-specific Cues In Mamentioning
confidence: 96%
“…Recent studies have shown that specific activation of aromatase neurons in the MeA promotes aggressive behaviors (Unger et al, 2015), and that reproductive sensory cues are processed by both the MeApv (Ishii et al, 2017) and the MeApd (Choi et al, 2005;Bergan et al, 2014). The overlapping control of aggressive and reproductive behaviors in the MeA mirrors the neuroethological argument that aggression is best understood as a component of reproductive behavior (Tinbergen, 1951).…”
Section: The Role Of Oxt In Mea Processing Of Sex-specific Cues In Mamentioning
confidence: 96%
“…This process could induce sex differences in gene expression in areas that do not express steroid hormone receptors. (c) A stimulus may activate distinct populations of neurons in the same brain area in males and females (Ishii et al, ), causing sex differences in both local activity‐responsive genes and in the two downstream target brain areas…”
Section: Crosstalk Between Hormone Signaling and Neural Activitymentioning
confidence: 99%
“…This process could induce sex differences in gene expression in areas that do not express steroid hormone receptors. (c) A stimulus may activate distinct populations of neurons in the same brain area in males and females (Ishii et al, 2017), causing sex differences in both local activityresponsive genes and in the two downstream target brain areas 9 | EMERGING THEMES: INTEGRATING FINDINGS ACROSS THE FIELD In this section, we will discuss a few recent publications that provide significant insight into the biology of sex differences in gene expression. Table 1 lists the brain regions studied and key genes identified in these papers, along with additional examples in which transcriptomic screens for sex differences were performed.…”
Section: Crosstalk Between Hormone Signaling and Neural Activitymentioning
confidence: 99%
“…Since SF1-expressing neurons have been shown to be activated by various predator cues, we analyzed the neural representation of ratCRP1 using cellar compartment analysis of temporal activity by fluorescence ISH (catFISH), with snake skin acting as a reference [32]. Unidentified compounds in snake skin activate mouse V2Rs and induce risk assessment behaviors in a manner that is dependent on a functional VNO [9,10].…”
Section: Ratcrp1 Signals Are Conveyed To the Medial Amygdala And Vmhmentioning
confidence: 99%